2001
DOI: 10.1016/s0010-4655(01)00214-4
|View full text |Cite
|
Sign up to set email alerts
|

Numerical consideration of quasilinear electron cloud dynamics in plasma

Abstract: The dynamics of a hot electron cloud in the solar corona-like plasma based on the numerical solution of kinetic equations of weak turbulence theory is considered.Different finite difference schemes are examined to fit the exact analytical solutions of quasilinear equations in hydrodynamic limit (gas-dynamic solution). It is shown that the scheme suggested demonstrates correct asymptotic behavior and can be employed to solve initial value problems for an arbitrary initial electron distribution function.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…The system of kinetic equations is reduced to dimensionless form and integrated using finite difference schemes. For the numerical time integration we used a method similar to the one used in [34] and the quasi-linear terms are integrated using methods described in [35]. Previous results [34,35] are found in full agreement with the corresponding limiting cases of our calculations.…”
Section: Numerical Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The system of kinetic equations is reduced to dimensionless form and integrated using finite difference schemes. For the numerical time integration we used a method similar to the one used in [34] and the quasi-linear terms are integrated using methods described in [35]. Previous results [34,35] are found in full agreement with the corresponding limiting cases of our calculations.…”
Section: Numerical Resultssupporting
confidence: 69%
“…For the numerical time integration we used a method similar to the one used in [34] and the quasi-linear terms are integrated using methods described in [35]. Previous results [34,35] are found in full agreement with the corresponding limiting cases of our calculations. The electron beam and plasma parameters are taken typical for the conditions in the solar corona [36,37].…”
Section: Numerical Resultssupporting
confidence: 69%
“…Zheleznyakov & Zaitsev 1970;Smith 1970;Zaitsev et al 1972;Smith et al 1976;Melrose 1980bMelrose , 1987Goldman 1983;Dulk 1985;Kontar et al 1998;Mel'Nik 2003;Ledenev et al 2004) and continues to develop with the advent of numerical simulations (e.g. Takakura & Shibahashi 1976;Magelssen & Smith 1977;Grognard 1985;Robinson 1992;Kontar 2001c;Li et al 2008;Kontar & Reid 2009;Tsiklauri 2010Tsiklauri , 2011Ratcliffe et al 2012;Li & Cairns 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies 17,18 indicated that these effects could be important. Those results rely on an entirely different computational model 60 based on the weak turbulence approximation. We have studied more localized density gradients in ion density, but these were of scale lengths too short to be relevant for those previous studies, 17,18 and no conclusive results can be presented.…”
Section: Discussionmentioning
confidence: 99%